Comparative Analysis of the Values of Traditional Business Entrepreneurs and Startup Founders - Alexey V. Zhuravlev; Maria A. Cheremenskaia (Lomonosov Moscow State University, 2023)
Background. Currently, the number of entrepreneurs who run traditional business or create a startup is growing. A startup is a special type of entrepreneurial activity that increases the risks of doing business. In this regard, the question of the personality traits of the entrepreneur who has a traditional business and the founder of the startup arises. Objective. The aim is to identify distinctive professional values of entrepreneurs who prefer traditional business (hereinafter referred to as TB entrepreneurs) and startup entrepreneurs. Methods. The hypotheses were tested by a survey including two test methods: the Rokich values method, a modified method from the Bushkova-Shiklina study. The paper compared the set of professional values of traditional business entrepreneurs (TB) and startup founders. Differences in values were checked through Pearson's chi-square calculation (χ2 ⸻ Pearson consent criterion). Sample. The sample consisted of 90 people. Of these, 46 participants (25 men and 21 women) are entrepreneurs, and 44 (27 men and 17 women) participants are startup founders living in Moscow and St. Petersburg. The age of respondents is from 20 to 40 years. Results. Statistically significant differences in the values of TB entrepreneurs and startup founders could not be found. The set of common values of TB entrepreneurs and startup founders is the same: interest in work, financially secure life, development. However, each group of entrepreneurs has its own specific values. TB entrepreneurs emphasise professionalism while startup founders emphasise success. Conclusions. TB entrepreneurs and startup founders have similar values. The personalities of TB entrepreneurs and startup founders have many similarities, similar values and directions in life, despite the fact that the activities of these two groups are not identical and have their own characteristics. A startup should be considered as a subtype of entrepreneurship. TB entrepreneurs demonstrate professionalism as a specific professional value. Startup founders have another specific professional value which is freedom.